Tourism carrying capacity of Singapore : are we reaching it? - Chua, Huimin. (2008)
Tourism is one of Singapore’s main pillars of growth. With tourist arrivals reaching record high in recent years, tourism has contributed greatly to Singapore’s revenue. However, the increasing amount of resources used to cope with increased tourism has also placed a burden on Singapore’s development and her tourism carrying capacity. Given the limited resources of Singapore, the benefits and consequences of tourism have to be weighted cautiously. The quality of living for the locals as well as the visitors’ experience can be greatly affected by an influx of tourists, if Singapore does not deal with the issue appropriately. However, if proper actions are taken, Singapore will benefit massively from tourism.